Providing Online Feedback Using an AI Proof-reading Tool to Enhance Student Surface-Level Writing Skills - Ester Widawati Tedjo (General English Education, 2022)
This study explores the use of an AI proofreading tool in providing feedback on surface features of student writing. It examines the effect of ProofWriter online feedback compared to teacher feedback on students’ writing improvement, and investigates which aspect of students’ surface-level writing skills improves the most after using the proofreading tool for two-months. Participants were 20 fourth-semester secretarial students taking English Business Correspondence II course. The ‘online group’ students used ProofWriter online tool to get feedback on surface-level aspects of their writing, and the ‘non-online group’ students got feedback from the class teacher while practicing to write English business letters. A pre-test and post-test were administered to show the students’ performance in writing the business letters. The letters were graded using the ESL Composition Profile rubric, and then means of the pre-test and post-test were calculated and T test was applied. A questionnaire about using ProofWriter online tool was distributed to the online group students. The results showed the online group students significantly increased their surface-level writing skills in a slightly higher level than those of the non-online group. They also improved the most in grammar for the surface features of writing.